More Than AI: Developing Intelligent Chatbot to Empower Algebra Mastery for Grade VII Students - Muhammad Nur Ramadhan; Abd. Qohar; Sisworo Sisworo; Mohamad Yasin (Universitas Suryakancana, 2026)
The challenge of learning algebra for junior high students necessitates innovative educational tools. This study aimed to develop and evaluate an intelligent chatbot, powered by a fine-tuned Mistral AI model, to empower algebra mastery for Grade VII students. R&D methodology using the ADDIE model was employed, involving one expert validator, 20 students, and 5 teachers for the evaluation. Data were collected through questionnaires and a post-test. The findings revealed that the chatbot was highly successful, achieving an expert validation score of 91.11% (